THE INFLUENCE OF FREE CASH FLOW, AUDIT COMMITTEE, MANAGERIAL OWNERSHIP AND FIRM SIZE ON FIRM VALUE WITH CORPORATE SOCIAL RESPONSIBILITY AS MODERATING VARIABLE IN BASIC INDUSTRY AND CHEMISTRY SECTOR COMPANIES LISTED IN INDONESIAN STOCK EXCHANGE - Nasution, Ananda Yusra (Asosiasi Dosen Akuntansi Indonesia, 2020)
The objective of the research was to analyze the influence of free cash flow, audit committee, managerial ownership, and firm size on firm value with Corporate Social Responsibility (CSR) as moderating variable. The population was 57 manufacture companies in basic industry and chemistry sector listed in BEI (Indonesia Stock Exchange) in the period of 2015-2017, and 40 of them were used as the samples, taken by using purposive sampling technique. The data were analyzed by using multiple linear regression analysis and residual analysis with E-views application program. The result of the research showed that free cash flow, audit committee, managerial ownership, and firm size on firm value partially and simultaneously had the influence on firm value. CSR as moderating variable could not moderate analyze the influence of free cash flow, audit committee, managerial ownership, and firm size on firm value.